2021
DOI: 10.21037/jtd-20-2409
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve replacement using the new Evolut-Pro system: a prospective comparison with the Evolut-R device

Abstract: Background: Evolut Pro (EVP) is a novel self-expandable aortic valve. This prosthesis consists of an external porcine pericardial wrap designed to reduce paravalvular leak (PVL), maintaining the benefits of its predecessor, the Evolut R (EVR). The aim was to compare the functional and clinical results in the short and medium term of the new EVP with the EVR system.Methods: Consecutive patients receiving either the EVR (n=50) or the EVP (n=33) from June 2015 to October 2018 were compared. Baseline characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Of these, 751 were excluded because they were not pertinent to the design of the meta-analysis or did not meet the explicit inclusion criteria. Eleven observational studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] (among them seven multi-center registries), including N = 12,363 patients, were eventually included in the analysis. Potential sources of study bias were analyzed with the use of the components recommended by the ROBINS-I tool, and the results are shown in Supplementary Table S2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 751 were excluded because they were not pertinent to the design of the meta-analysis or did not meet the explicit inclusion criteria. Eleven observational studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] (among them seven multi-center registries), including N = 12,363 patients, were eventually included in the analysis. Potential sources of study bias were analyzed with the use of the components recommended by the ROBINS-I tool, and the results are shown in Supplementary Table S2 .…”
Section: Resultsmentioning
confidence: 99%
“… Risk Ratios (RRs) and corresponding 95% Confidence Intervals (CIs) for the comparison of Evolut PRO and Evolut R devices [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]; ( A ) moderate-to-severe paravalvular leak; ( B ) mild paravalvular leak. Each square represents study point estimate; diamonds reflect the overall effect.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the newer generation THVs, including Edwards SAPIEN-3 and Evolut Pro valves, have the development of an outer skirt that can deliver a better seal, resulting in a lower PVL risk, which is a common risk factor for long-term mortality in patients undergoing TAVR. Even in patients who develop at least moderate PVL after TAVR, the study showed that this population had a regression of PVL at the one-year follow-up [ 34 , 35 ]. Additionally, the pacemaker placement rates decreased with SAPIEN-3 and Evolut R, which deployed the valves at higher implantation heights.…”
Section: Discussionmentioning
confidence: 99%